Understanding preferences for type of take-home naloxone device: international qualitative analysis of the views of people who use opioids. (4th March 2022) - Neale, Joanne; Farrugia, Adrian; Campbell, Aimee N.; Dietze, Paul; Dwyer, Robyn; Fomiatti, Renae; Jones, Jermaine D.; Comer, Sandra D.; Fraser, Suzanne; Strang, John
Abstract: Background: Take-home naloxone (THN) is provided to non-medically trained people to reverse potential opioid overdoses. There is an increasing range of effective intramuscular (IM) and intranasal (IN) naloxone devices and this paper explores the types preferred by people who use opioids, using consumer behaviour literature to interpret the findings. Methods: Data derive from two unconnected qualitative studies involving audio-recorded semi-structured interviews. Study 1 was conducted in the United States ( n = 21 users of non-medical/illicit opioids). Study 2 was conducted in Australia ( n = 42 users of non-medical/illicit or prescribed opioids). Findings: Most participants preferred IN naloxone. Preferences were based on the ease, speed, safety and comfort of each device and underpinned by accounts of overdose revivals as being very rushed and frightening situations. Preferences related to complex interactions between the naloxone device ('product'); the knowledge, skills, experience and attitudes of the lay responder ('consumer'), and when, where and how naloxone was to be used ('usage situation'). Conclusions: THN programs should offer choice of device when possible and nasal naloxone if resources permit. Asking people which devices they prefer and why and treating them as valued consumers of naloxone products can generate insights that improve future naloxone technology and increase THN uptake and usage.